PATHOMORPHOLOGICAL CHANGES OF RESPIRATORY DEPARTMENT OF LUNGS DUE TO MULTIPLE SKELETAL TRAUMA WITH THE USE OF INTRAMEDULLARY OSTEOSYNTHESIS IN THE EXPERIMENT - Zaiats, L.M.; Kuz, U.V. (World of Medicine and Biology, 2018)
Experimental study was carried out on 90 white male Wistar line rats and defined microscopic and ultrastructural changes of the respiratory department of the lung due to multiple skeletal trauma with intramedullary osteosynthesis use in dynamics (6, 24, 72, 168 hours) by lightoptical and electron microscopic methods. It was proved that intramedullary osteosynthesis of the femoral bones bring on severe changes of the structural organization of all components of the respiratory department of the lungs during the first 24 hours after the trauma. In the respiratory department there was both dystrophic-destructive and compensatory-adaptive changes during 72-168 hours of the study.